A Convenient Synthesis and Biological Research of Novel 5, 6, 7, 8‐Tetrahydro‐1, 6‐naphthyridin‐2(1H)‐one Derivatives Hydrochloride as Cytotoxic Agents. (13th July 2018) - Xu, Guiqing; Gao, Yuan; Sun, Bin; Peng, Lizeng; Mao, Longfei; Jiang, Yuqin; Ding, Qingjie
Abstract : A series of 5, 6, 7, 8‐tetrahydro‐1, 6‐naphthyridin‐2(1 H )‐one derivatives hydrochloride were obtained using a convenient and mild method from 4‐piperidone monohydrate hydrochloride. The newly synthesized compounds and their derivatives were characterized by 1 H NMR, 13 C NMR, and high‐resolution mass spectrometry. Furthermore, cytotoxicity in vitro of the synthesized compounds were screened using MTT or CCK8 assay. The results showed that some of the compounds showed potential antitumor activity. Among of them, compound10a had effects against tumor cells (MOLM‐13), and the half maximal inhibitory concentration value was 76 μmol/L. Abstract :